Optical Simulation Study of Perovskite/CIGS Tandem Solar Cells With Reduced Graphene Oxide Layers - Kovačič, Milan; Krč, Janez; Savva, Kyriaki; Maragkaki, Stella; Stratakis, Emmanuel; Rashid, Mudasar; Tutundzic, Merve; Kuang, Yinghuan; de Wild, Jessica; Aernouts, Tom; Vermang, Bart; Topič, Marko (Frontiers in Photonics, 2022)
Tandem solar cells present a promising solution to overcome the Schottky–Queisser efficiency limit of single-junction solar cells. In this article, an all–thin-film tandem solar cell based on perovskite (PK) top cell and chalcopyrite Cu (In, Ga) Se2 (CIGS) bottom cell is researched. Device optical simulations are validated on the top and bottom cells and employed for the analysis of PK/CIGS tandem cells. In particular, the optical effects of introduced laser reduced graphene oxide (rGO) layers at two positions in the tandem cell: 1) at the position between the top PK and bottom CIGS cell and 2) underneath the front transparent electrode. The purpose of introducing rGO layers is to improve the optoelectrical properties of the device, based on the tunable electronic and optical characteristics of rGO layers. Optical simulation results show that the parasitic absorption in rGO layers may noticeably affect the optical performance of the tandem cell if the layers are not optimized. The use of a thin and a few nanometer-thick rGO is suggested from the analysis if its parasitic absorption is not reduced. Directions for further optimization of optical rGO, including the reduction of parasitic absorption and tuning of the real part of the refractive index, are performed.